2018
DOI: 10.1007/s13197-018-3245-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of live and heat-killed probiotic Lactobacillus plantarum Ln1 isolated from kimchi

Abstract: The aim of this study was to evaluate the probiotic properties of Ln1 isolated from kimchi and the antioxidant activities of live and heat-killed cells. KCTC 3108, which has been used as a commercial probiotic strain, was used as a control. strains (Ln1 and KCTC 3108) can survive under artificial gastric conditions (pH 2.5 in 0.3% pepsin for 3 h and 0.3% oxgall for 24 h), and adhere strongly to HT-29 cells. In addition, Ln1 did not produce carcinogenic β-glucuronidase, whereas it showed a higher β-galactosidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 24 publications
0
40
0
1
Order By: Relevance
“…As a result, heat-killed L. fermentum KU200060 and L. buchneri KU200793 showed higher antioxidant activity than heat-killed L. delbrueckii KU200171. Heat-killed L. plantarum Ln 1 showed 17.60% DPPH radical scavenging activity, 70.18% ABTS radical scavenging activity, and 58.3% inhibition rate of lipid peroxidation at 10 7 CFU/mL [11]. L. acidophilus ATCC 4356 showed 20.8% of DPPH radical scavenging activity in intracellular extract [29].…”
Section: Antioxidant Effects Of Heat-killed Lab Strainsmentioning
confidence: 93%
See 1 more Smart Citation
“…As a result, heat-killed L. fermentum KU200060 and L. buchneri KU200793 showed higher antioxidant activity than heat-killed L. delbrueckii KU200171. Heat-killed L. plantarum Ln 1 showed 17.60% DPPH radical scavenging activity, 70.18% ABTS radical scavenging activity, and 58.3% inhibition rate of lipid peroxidation at 10 7 CFU/mL [11]. L. acidophilus ATCC 4356 showed 20.8% of DPPH radical scavenging activity in intracellular extract [29].…”
Section: Antioxidant Effects Of Heat-killed Lab Strainsmentioning
confidence: 93%
“…Kimchi is a Korean traditional fermented food, containing biologically active components including polyphenols, vitamins, flavonoids, and lactic acid bacteria (LAB) [11]. Various kinds of microorganisms, including Leuconostoc sp., Lactobacillus sp., and Lactococcus sp., are mainly found in kimchi.…”
Section: Introductionmentioning
confidence: 99%
“…Since the specific action of postbiotics relies on definite dosage levels, most studies have failed to fix a specific dose of postbiotics/paraprobiotics to ensure the beneficial effects alike probiotics at 10 9 viable cells. To investigate the effectiveness of postbiotics, currently, there have been a handful of comparative studies conducted at the in vitro and in vivo levels, and such studies suggest the similar potentialities of postbiotics over the probiotics in terms of demonstrating various health benefits on the host [ 35 37 ]. Singh et al have reported an excellent antagonistic knack of paraprobiotics (heat-killed form) over the live probiotic bacteria against enteropathogens [ 38 ].…”
Section: Concepts and Definitionmentioning
confidence: 99%
“…Additionally, several heat-killed probiotics strains of Lactobacillus have demonstrated the anti-inflammatory (ability to suppress the inflammatory markers like IL-6, TNF- α and to enhance anti-inflammatory cytokines viz. IL-10) and anti-oxidative (ability to scavenge the free radicals) effects at in vitro and in vivo experimental models [ 35 , 53 ]. On the other hand, probiotic heat-killed preparation had a substantial influence over serotonin secretion in the gut (gut-brain axis) [ 54 ].…”
Section: The Forms Of Postbiotics and Paraprobioticsmentioning
confidence: 99%
“…The ABTS assay for antioxidant activity of LAB was carried out as described by Jang et al [18] with minor modifications. The ABTS solution was prepared by mixing 14 mM ABTS and 5 mM potassium persulfate in 0.1 M potassium phosphate buffer (pH 7.4) and incubated at 25°C for 12-16 h under dark conditions.…”
Section: -Azinobis-(3-ethylbenzothiazoline-6-sulfonic Acid) (Abts) Rmentioning
confidence: 99%